Comparing and Deciding: a historical note on education policy - Magalhães, Justino (2014)
This article gives the lineage of education policy decisions, taking comparison as the motive, knowledge and method. A conceptual chain of the world system, internationalization, convergence in education and globalization is briefly outlined. Decision in education policy is discussed in terms of agreeing, mainstreaming, and producing, taking Latin America as the linkage and the European Community as the construction. Reasoning and illustration are gathered in different fields of history: cultural, economic, political, educational. Use is made of a core structuring epistemology, culled from a variety of academic domains and in which comparison and decision underpin a complex rationale in which time, space, materiality, knowledge, ideation, action and evaluation all intersect